Partnership strategy and guidelines for pt. Pjb in 35.000 mw market - Firmansyah, Roby; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2016)
Abstract - PT Pembangkitan Jawa Bali (PT PJB) is a subsidiary company of PT PLN engaged in power generation business. From 2005-2020, energy market of Java Bali System trend and projection shows a promising growth. The demand of electricity is increasing but PJB’s market share is going down from year to year until year 2020 (7.2%). The decreasing market share was contributed by the growth of the energy market and the stagnancy of PJB existing power plant capacity and sales. Government of Indonesia gives big portion to IPP (25.000 MW) rather than PLN (10.000 MW) in the 35.000 MW project. In order to increase the PJB market share, it is required internal and external analysis to formulate their business strategies. The strategy formulation begins from analysing the external and internal environment using several methods such as PEST analysis, Porter’s Five Forces Analysis and Resource Based View analysis to generate the SWOT analysis. The EFAS and IFAS result then used to determine the current position of PT PJB in the SWOT Matrix Diagram. The result indicates that PT PJB is in the cell I that interpreted as supports an aggressive strategy to grow. The Ansoff matrix and QSPM are used to analyse the most appropriate strategy in entering new market (35.000 MW) and the result is partnership strategy. As the selected strategy, it may need proper guidelines in project and partner selection. The good implementation and dissemination plan will result of the success of partnership strategy. Keywords: Business Strategy, Independent Power Producers, Partnership Strategy, Partner selection